Penggunaan Teleconference Dalam Pelaksanaan Tugas Jabatan Notaris Pada Masa Pandemi Berdasarkan Undang-Undang Jabatan Notaris - Muhammad Roem Abdurrahman (Officium Notarium, 2022)
This article aims to examine the use of teleconferences in carrying out the duties of a notary public office during a pandemic based on the Notary Office Law. This type of research is empirical legal research with 4 (four) Notaries in the Special Region of Yogyakarta as resource persons. The results of this study conclude that the use of a teleconference during a pandemic is a legal interpretation of cyber notary regulations in the UUJN, and the physical absence of a notary at the formalization of a deed is not a violation of Article 17 UUJN. The use of a teleconference does not violate the law as long as it is carried out based on applicable legal provisions and fulfills the formal and material requirements of a deed.Key Word: Duties and Positions of Notary, Teleconference, Pandemic AbstrakArtikel ini bertujuan untuk mengkaji penggunaan teleconference dalam pelaksanaan tugas jabatan notaris pada masa pandemi berdasarkan Undang-Undang Jabatan Notaris. Jenis Penelitian ini adalah penelitian hukum empiris dengan 4 (empat) Notaris di Daerah Istimewa Yogyakarta sebagai narasumber. Hasil penelitian ini menyimpulkan bahwa penggunaan teleconference selama masa pandemi merupakan sebuah penafsiran hukum atas peraturan cyber notary dalam UUJN, serta ketidak hadiran fisik dari notaris dalam peresmian akta bukan merupakan pelanggaran Pasal 17 UUJN. Penggunaan teleconference tidak melanggar hukum selama tetap dilaksanakan berdasarkan ketentuan hukum yang berlaku dan memenuhi syarat formil dan materil dari sebuah akta.Kata-kata Kunci: Tugas dan Jabatan Notaris Teleconference, Pandemi